Parâmetros relacionados à depressão em camundongos adultos submetidos à malária cerebral no período infanto - Freiberger, Viviane (2018)
Introduction: Cerebral malaria (CM) is among the main causes of mortality associated with malaria. There are reports that MC survivors may develop long-term neurocognitive deficits. Studies have shown the role of neuroinflammation in the development of depression. Neuroinflammation can significantly modulate encephalic development, immune and endocrine regulation, as well as neural circuits, resulting in physiological and behavioral changes. Objective: To evaluate parameters related to depression in adult mice submitted to cerebral malaria in the infantile period. Methods: C57BL/6 animals at 21 days of age were infected with Plasmodium Berghei ANKA. After six days of infection, these animals were treated with chloroquine for seven days and at 46 days of life received PBS or Imipramine for 14 days. At 60 days of life, the consumption of sucrose was evaluated; the time of immobility; weight, volume of the adrenal gland and hippocampus; the corticoesterone and hippocampal plasma levels of BDNF and IL-1β. Results: It can be observed that the animals exposed to MC in the infantile period and evaluated in the adult life showed an increase of the immobility time; an increase in adrenal gland volume, an increase in plasma corticosteroid levels, a reduction in hippocampal volume; a decrease in BDNF levels in the hippocampus and an increase in levels of IL-1 in the hippocampus. Among the parameters evaluated, only IL-1β levels were not reversed with antidepressant use. The weight of the animals and the sucrose preference test were also evaluated, however, they did not present a significant difference between the groups. Conclusion: These results suggest that immune activation in the infantile period may be associated with parameters related to depression in adult life.